2013
DOI: 10.1080/13504622.2013.833596
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood educators’ use of natural outdoor settings as learning environments: an exploratory study of beliefs, practices, and barriers

Abstract: In efforts to encourage use of natural outdoor settings as learning environments within early childhood education, survey research was conducted with 46 early childhood educators from northern Minnesota (United States) to explore their beliefs and practices regarding natural outdoor settings, as well investigate predictors of and barriers to the educational use of these settings. Of the beliefs measured, only two were significantly related to frequency of use of natural outdoor settings: belief regarding diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 37 publications
4
64
1
8
Order By: Relevance
“…In earlier research on challenges and opportunities associated with implementing OLEs, access to outdoor settings for teaching and learning emerged as a barrier to use (Ernst, 2014). In this study, access was not a barrier as the OLE was located on-site, was purposefully designed for use by teachers and students, and was easily accessible.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In earlier research on challenges and opportunities associated with implementing OLEs, access to outdoor settings for teaching and learning emerged as a barrier to use (Ernst, 2014). In this study, access was not a barrier as the OLE was located on-site, was purposefully designed for use by teachers and students, and was easily accessible.…”
Section: Discussionmentioning
confidence: 86%
“…Despite a general appreciation of the value of OLEs, many early childhood educators face barriers, both perceived and real, to implementing learning outdoors. Ernst (2014) found that while teacher beliefs regarding one's relationship with nature shows a positive correlation with the frequency of use of OLEs, it did not have a significant influence on use in relation to other belief variables. Ernst (2014) found that the most significant predictor of outdoor use are beliefs regarding perceived difficulties in using OLEs.…”
Section: Literature Reviewmentioning
confidence: 77%
See 2 more Smart Citations
“…Hainbat arrazoi daude hori horrela izateko, hala nola, teknologiak, trafikoa, eguraldia eta hezkuntza erakundeak (Doucette, Kowalski eta Ransom, 2007;Ernst 2014; Fdzila eta Said;2010; Maynard eta Waters, 2007). Teknologiari dagokionez, haurrak gero eta lehenago hasten dira horiek erabiltzen, eta sasoi batean kanpoan ematen zuten denbora nolabait ordezkatu egin dute (Doucette et al, 2007).…”
Section: Sarreraunclassified